2014
DOI: 10.3389/fnhum.2014.00475
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar contribution to feedforward control of locomotion

Abstract: The cerebellum is an important contributor to feedforward control mechanisms of the central nervous system, and sequencing—the process that allows spatial and temporal relationships between events to be recognized—has been implicated as the fundamental cerebellar mode of operation. By adopting such a mode and because cerebellar activity patterns are sensitive to a variety of sensorimotor-related tasks, the cerebellum is believed to support motor and cognitive functions that are encoded in the frontal and parie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 47 publications
2
55
1
Order By: Relevance
“…This approach improves upon commonly used seed-based approaches by enabling network-level conclusions to be drawn, obviating susceptibility to biases related to variations in seed positioning, and eliminating the requirement of a priori hypotheses about particular brain regions (Buckner et al, 2008; Cole et al, 2010b). In the current study, across all participants and medication conditions, we observed higher FCD in regions comprising the default mode network (PCC/precuneus, VMPFC) (Andrews-Hanna et al, 2010; Buckner et al, 2008), in regions central to information processing and cortico-striatal-thalamo-cortical communication (thalamus) (Jakab et al, 2012), and in regions central to motor coordination and action plans (cerebellum, sensorimotor cortex) (Hardwick et al, 2013; Pisotta and Molinari, 2014), all purported to serve as critical brain hubs.…”
Section: Discussionsupporting
confidence: 47%
“…This approach improves upon commonly used seed-based approaches by enabling network-level conclusions to be drawn, obviating susceptibility to biases related to variations in seed positioning, and eliminating the requirement of a priori hypotheses about particular brain regions (Buckner et al, 2008; Cole et al, 2010b). In the current study, across all participants and medication conditions, we observed higher FCD in regions comprising the default mode network (PCC/precuneus, VMPFC) (Andrews-Hanna et al, 2010; Buckner et al, 2008), in regions central to information processing and cortico-striatal-thalamo-cortical communication (thalamus) (Jakab et al, 2012), and in regions central to motor coordination and action plans (cerebellum, sensorimotor cortex) (Hardwick et al, 2013; Pisotta and Molinari, 2014), all purported to serve as critical brain hubs.…”
Section: Discussionsupporting
confidence: 47%
“…This behavioral anticipation is copied into and reconstructed by an internal model in the cerebellum. This internal model of predictable patterns of behavior and learned social responses allows us to act automatically and socially adept each time we see our neighbor (Ito, 2008;Pisotta and Molinari, 2014). Now, if our neighbor disconfirms our internal model by making a friendly gesture, such a mismatch leads to an error signal that corrects the ongoing social interaction as well as the relevant internal model in the cerebellum.…”
Section: Discussionmentioning
confidence: 89%
“…This role of internal sequencing predictions is perhaps most prominent in mental reconstructions of autobiographic past, future or hypothetical events, and in inferring traits and stereotypes from a person's behavior or a group's actions. While the cerebellum makes these internal sequencing predictions based on input from the cerebrum, they must be matched on-line against information from external sources to check their plausibility, and to send error signals if mismatches occur (Ito, 2008;Pisotta and Molinari, 2014). Thus, signals from the cerebellum might continuously check whether an anticipated event based on (abstract) social information fits with current behavior.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The RMTg is a recent addition to the important connectional partners of the VTA (Jhou et al, , ,; Perrotti et al, 2007; Kaufling et al, ; Balcita‐Pedicino et al, ) with significant functional and behavioral associations that presently are mainly regarded as reflecting its role in relaying the influence of the LHb to the VTA, particularly as regards reward omission and responses to aversive stimuli (Jhou et al, , ; Lecca et al, , ; Hong et al, ; Matsui and Williams, ; Matsui et al, ). However, modulation of midbrain DAergic activity by the RMTg may transcend this limited role, insofar as injections of tracer into the RMTg, as compared to the VTA and LHb, produced significantly more retrogradely labeled neurons in cerebellar nuclei, deep layers of the superior colliculus contralateral to the tracer injection, retrorubral field, pontine reticular formation, dorsomedial tegmental area, and raphe interpositus—all structures that have been shown or are thought to have significant roles in regulating motor, including visuomotor, function (e.g., Sahibzada et al, ; Dean et al, ; von Krosigk and Smith, ; Newman and Ginsberg, ; von Krosigk et al, ; Arts et al, ; Arts and Cools, , , ; Isa and Sasaki, ; Colussi‐Mas et al, ; Hittinger and Horn, ; Pisotta and Molinari, ; Thach, ). Consistent with previous studies (Jhou et al, ,; Kaufling et al, ), the present data also identified the VP‐LPO‐LH continuum as a major input to the RMTg (see also Zahm et al, ), stimulation of which is often reported to powerfully activate locomotion (Mogenson and Nielsen, ; Mogenson et al, , , ; Shreve and Uretsky, , , ; Austin and Kalivas, , , ; Kalivas et al, ; Mogenson and Yang, ; Willins et al, ; Johnson et al, ; Gong et al, ; Johnson and Napier, ; Chen et al, ; June et al, ; Hubert et al, ; Zahm et al, …”
Section: Discussionmentioning
confidence: 99%